1990
DOI: 10.1111/j.1476-5381.1990.tb12048.x
|View full text |Cite
|
Sign up to set email alerts
|

Inositol phospholipid hydrolysis in human brain; adenosine inhibition of the response to histamine

Abstract: Inositol phospholipid hydrolysis was examined in human cerebral cortex slices by a [3H]‐inositol prelabelling assay. Enhancement of [3H]‐inositol phosphates accumulation was observed in the presence of carbachol, noradrenaline, histamine, 5‐hydroxytryptamine (5‐HT) and depolarizing concentrations of KCl. Despite having no effect alone, adenosine (and its analogue 2‐chloroadenosine) selectively inhibited the direct response to histamine. The inhibition due to adenosine was antagonized by theophylline, but not b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

1991
1991
1996
1996

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 14 publications
2
2
0
Order By: Relevance
“…H2-receptors and a potentiation of that response by Hrreceptors (Baudry et al, 1975). We have previously shown that phospholipase C-linked HI-receptors are active in human brain slices (Kendall & Firth, 1990) and, as demonstrated in this study, HI-receptors potentiate the effects of P-adrenoceptor activation, so the ineffectiveness of histamine alone is probably due to a low density of directly coupled H2-receptors in human cortex.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…H2-receptors and a potentiation of that response by Hrreceptors (Baudry et al, 1975). We have previously shown that phospholipase C-linked HI-receptors are active in human brain slices (Kendall & Firth, 1990) and, as demonstrated in this study, HI-receptors potentiate the effects of P-adrenoceptor activation, so the ineffectiveness of histamine alone is probably due to a low density of directly coupled H2-receptors in human cortex.…”
Section: Discussionsupporting
confidence: 74%
“…The response to isoprenaline was also potentiated by histamine acting, on the evidence of the affinity for mepyramine, through an HI-receptor. The IC50 for this effect of mepyramine (35 nM) was very similar to that found previously for the inhibition of histamine-stimulated phosphoinositide hydrolysis in human brain (Kendall & Firth, 1990) and it is possible that the same HI receptors are involved. This particular example of potentiation would appear to be unique to human brain, at least amongst those species examined to date, and might simply reflect the colocation of P-adrenoceptors and HI-receptors.…”
Section: I-t-l-supporting
confidence: 84%
“…However, it is clear that not all brain tissues show the same very marked dependence on extracellular Ca2+ as mouse and rat cerebral cortex and the Ca2`-dependence observed in the U373 MG cells is much closer to that in the guinea-pig tissues. There is as yet no indication whether this is also the pattern in human cerebral cortex, a tissue in which histamine is known to stimulate phosphoinositide hydrolysis (Kendall & Firth, 1990) and it would be unwise to make predictions on the basis of the response in a transformed cell line.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, adenosine inhibited norepinephrine-enhanced phosphoinositidc hydrolysis in rat aorta (Long and Stone, 1987). Further, in cerebral cortex preparations, histamine-, but not norepinephrine-or carbamylchol me-, stimulated phosphoinositide tumover was either augmented or attenuated by adenosinereceptor activation (Hollingsworth et al, 1986;Hill and Kendall, 1987;Kendall and Hill, 1988;Alexander et al, 1989;Kendall and Firth, 1990).…”
Section: Discussionmentioning
confidence: 99%